Non-dimensional analysis of shot peening by means of DoE. (1st January 2000) - Baragetti, S.; Terranova, A.
Shot peening is widely used to improve the fatigue properties of mechanical components cyclically loaded; the benefits of the treatment, mainly due to the compressive residual stress field induced in the surface layers of material, depend on the correct choice of the peening parameters. "Design of Experiments" (DoE) was applied to the results obtained from the numerical simulation of shot peening (impact of one or more spheres on smooth steel targets), and used to choose the best levels of the treatment parameters in a cheap and fast way. Non-dimensional parameters were defined and used to generalise the results obtained from the analyses carried out on steel targets and this enabled the choice of the peening parameters for different treatment conditions and several treated materials.